Development and optimization of High-Hertz stress contact to reduce future contact material cost - Bhuiyan, Moinul (2010)
Reducing a total contact material cost of a connector, a high-Hertz stress with low normal force (LNF) contact will be a key technology in the future. Only an R5m tip with 0.1N force contact provides an excellent electrical performance which is much sharper than conventional connectors. 0.30 million cycles durability test was passed and the contact resistance was ≦50m-ohm.